Criteria for Effective Communication – Communication Barriers (Disqualified Messages, Cognitive Dissonance and Incongruence) - Lubinszki, Mária (Interdisciplinary and Child-Friendly Communication, 2025)
The art of child-friendly communication is a complex, multi-factorial process in which the use of specific communication techniques by adults, adapted to the needs of the child and the situation, is of utmost importance. This is only effective if one is familiar with the theories and practical techniques of effective communication, if one knows oneself and is mentally sound, and if one recognises the barriers and obstacles to communication. The most difficult point in any human relationship and situation management is dealing with uncertainty and resistance. Disqualified messages, cognitive dissonance, and incongruent communication have in common that they create anxiety, make us feel insecure, and make it difficult to connect with the other person. The persistence of such a tensioninducing, subordinating pattern of communication may even leave residual and permanent traces in personality development. This chapter provides a theoretical and practical insight into this.Keywords: effective communication, communication competences, communication barriers, cognitive dissonance, incongruence